Renting at the Edge of the World: Climate Change Protections Failing Renters - Clara Potter; Lauren Godshall (Washington University Journal of Law and Policy, 2024)
American law and policy are designed to protect property owners. Unsurprisingly, this extends to the policies and laws that are developing in response to climate change. Renters, however, are a massive part of the population, particularly in the places most likely to be impacted in the near and long-term by the effects of climate change. Yet governments at every level currently condition benefits—whether relief for damage caused by natural disasters or proactive funding incentives to develop new climate-safe infrastructure—on property ownership. Because this paradigm centers ownership and the protection of property wealth, renters are largely overlooked. People of color and lower-income households tend to be renters, and so this regime further entrenches existing inequalities and environmental racism, depriving those most in need from access to resources to plan for climate adaptation. The current system not only perpetuates existing racial inequities but also does not make economic sense in the short or long term. The sooner renters are prioritized, the more effective and fair the transition toward a climate response that protect all human life can be. This article first lays out the disparate historical treatment of renters and property owners, and explains how existing and future climate change protections are compounding, rather than aiding, inequities in housing. A survey of current policies available for renters at the federal, state, and local levels makes these gaps visible and underscores the need for a shift in equitable climate change planning, one that centers protection for non-property owners. Existing policy and legal tools can and must be creatively adapted to effectively respond to climate change while including renters. This article attempts to fill a silence in existing literature and to address gaps in policy and legal frameworks. It then posits some high-level solutions to bridge those gaps. By advancing better policy—including, most importantly, building new, resilient public housing units—and by leveraging existing litigation tools, governments at every level can better protect renter populations facing our new climate reality. This is necessary to ensure that all communities and individuals—regardless of property ownership status—are protected from the advance of climate change and can be included in equitable adaptation and mitigation efforts.
Keywords: ClimateAdaptation; RentersRights; EnvironmentalRacism; HousingInequality; EquitableClimatePolicy